DEEDS NOT WORDS: AMERICAN SOCIAL JUSTICE MOVEMENTS AND WORLD WAR I. (27th September 2018) - Keene, Jennifer D.
Abstract : This essay investigates how the repressive wartime political and social environment in World War I encouraged three key American social justice movements to devise new tactics and strategies to advance their respective causes. For the African American civil rights, female suffrage, and civil liberties movements, the First World War unintentionally provided fresh opportunities for movement building, a process that included recruiting members, refining ideological messaging, devising innovative media strategies, negotiating with the government, and participating in nonviolent street demonstrations. World War I thus represented an important moment in the histories of all three movements. The constructive, rather than destructive, impact of the war on social justice movements proved significant in the short term (for the suffragist movement) and the long term (for the civil rights and civil liberties movements). Ultimately, considering these three movements collectively offers new insights into American war culture and the history of social movements.